Educational interventions to improve quality of life in people with chronic inflammatory skin diseases: systematic reviews of clinical effectiveness and cost-effectiveness - Karen Pickett; Emma Loveman; Neelam Kalita; Geoff K Frampton; Jeremy Jones (Health Technology Assessment, 2015)
Background: Inflammatory skin diseases include a broad range of disorders. For some people, these conditions lead to psychological comorbidities and reduced quality of life (QoL). Patient education is recommended in the management of these conditions and may improve QoL. Objectives: To assess the clinical effectiveness and cost-effectiveness of educational interventions to improve health-related quality of life (HRQoL) in people with chronic inflammatory skin diseases. Data sources: Twelve electronic bibliographic databases, including The Cochrane Library, MEDLINE and EMBASE, were searched to July 2014. Bibliographies of retrieved papers were searched and an Advisory Group contacted. Review methods: Systematic reviews were conducted following standard methodologies. Clinical effectiveness studies were included if they were undertaken in people with a chronic inflammatory skin condition. Educational interventions that aimed to, or could, improve HRQoL were eligible. Studies were required to measure HRQoL, and other outcomes such as disease severity were also included. Randomised controlled trials (RCTs) or controlled clinical trials were eligible. For the review of cost-effectiveness, studies were eligible if they were full economic evaluations, cost–consequence or cost analyses. Results: Seven RCTs were included in the review of clinical effectiveness. Two RCTs focused on children with eczema and their carers. Five RCTs were in adults. Of these, two were of people with psoriasis, one was of people with acne and two were of people with a range of conditions. There were few similarities in the interventions (e.g. the delivery mode, the topics covered, the duration of the education), which precluded any quantitative synthesis. Follow-up ranged from 4 weeks to 12 months, samples sizes were generally small and, overall, the study quality was poor. There appeared to be positive effects on HRQoL in participants with psoriasis in one trial, but no difference between groups in another trial in which participants had less severe psoriasis. Carers of children in one RCT of eczema showed improvement in HRQoL; however, in a RCT evaluating a website intervention there were no demonstrable effects on HRQoL. Neither the RCT in those adults with acne nor the RCT in those adults with mixed skin conditions demonstrated an effect on HRQoL. One RCT reported subgroups with atopic dermatitis or psoriasis and education was effective for psoriasis only. Other outcomes also showed mixed results. It is unclear how clinically meaningful any of the observed improvements are. Three studies of cost-effectiveness were included. The interventions, comparators and populations varied across the studies and, overall, the studies provided limited information on cost-effectiveness. The studies did provide detailed information on resources and costs that could be useful to inform a future cost-effectiveness evaluation in this area. Limitations: The application of the inclusion criterion around whether the interventions were aimed at improving HRQoL or the inference that they could improve HRQoL was difficult as information was rarely reported. Conclusions: There is uncertainty regarding whether educational interventions addressing issues that could improve HRQoL in people with chronic skin conditions are effective. Tentative conclusions about the best approach to delivering these kinds of interventions are that face-to-face, group, sessions may be beneficial; however, text messages may also be effective. Delivery over a period of time and by a multidisciplinary team may also be associated with positive outcomes. There is uncertainty over whether or not educational interventions are cost-effective. Study registration: This study is registered as PROSPERO CRD42014007426. Funding: The National Institute for Health Research Health Technology Assessment programme.